Understanding the population trends of shorebirds within New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Ecology at Massey University, Manawatū, New Zealand - Mowbray, Liam Patrick (Massey University, 2023)
The study investigated population trends of 10 shorebird species in New Zealand, using historic counts from the Ornithological Society of New Zealand dating from 1960- 2021. The initial dataset contained counts of 27 shorebird species at 854 local sites within 115 main sites. Minimum population and count cut-offs were created for each species at each main site for winter (June/July) and summer (November/December) census counts, which reduced the final dataset to 10 species (six northern hemisphere-breeding species and four New Zealand-breeding species) at 2–32 sites depending on the season. Generalised Additive Models were used to model count trends over time for each species at each relevant site and season. From these models, population trends for different time periods were extracted: 1990s onwards, 2000s onwards, 2010s onwards, from the first year surveyed and from the year of maximum count. These trends were then used to test if, across the different sites, trends were significantly different to zero (i.e., did trends tend to be negative or positive over each time period). Linear models were then used to test whether site-specific trends varied with local population size (the maximum count), site area (estimated from aerial imagery) and latitude. The aim was to determine if trends varied in a way consistent with a buffer effect, in which population change is greater at low-quality sites (here being sites with smaller populations) than at high-quality sites. Results showed that while trends varied over time for most species at most sites, there was little evidence of a buffer effect. However, trends of northern hemisphere species were more adversely affected than those of internal migrants with 14 time periods of significant decline for the arctic migrants in comparison to 8 time periods of significant decline for the internal migrants.
Keywords: 310307 Population ecology